Prevalence of Head Lice in Jeddah City, Saudi Arabia According to Crowding Criteria (Journal of Basic and Applied Research in Biomedicine, 2022)
One of the cosmopolitan parasites recorded all over the world is the Head Lice, Pediculus humanus capitis, it parasitizes the human being with highly prevalent in children. The habit feeding of Head lice is sucking blood from human and it is about every 4 to 6 hours each day which causing severe irritation and inflammation. Crowding is the factor effect on the prevalence of Pediculus humanus capitis between hosts, this record is related to the crowding factor increased the head lice prevalence among school girl students attending the elementary schools in Jeddah city. Study was conducted by filling the questionnaires for the head lice infected students in the public and private schools under study according to their information in the schools records. The Pediculus humanus capitis infested students were mainly lived in apartments have at least three rooms. The student's siblings was five or more, most of them sharing their sister in bed and having prior infested people in the student's family.